Business Attributes and Marketing Communication Strategies of SMEs in South Africa - Ramasobana, Morongwa; Fatoki, Olawale (Journal of Economics and Behavioral Studies, 2018)
The purpose of this study was to investigate business attributes and marketing communication practices of SMEs in South Africa. This study adopted the quantitative research design with a descriptive research method. Data was collected through the use of self-administered questionnaires in a survey. Descriptive statistics, ANOVA and regression analysis were used to analyse data. The results revealed that some marketing communication tools indicate that there is no significant difference in the marketing communication tools adopted by SMEs on the basis of business attributes. In addition, some marketing communication tools indicated that there is a significant difference in the marketing communication tools adopted by SMEs on the basis of business attributes. This study recommended that SMEs’ owners should consider their business factors when selecting the marketing communication strategies and equip themselves with the knowledge of marketing communication.